Using Fluridone Herbicide Systems for Weed Control in Texas Cotton (Gossypium Hirsutum L.): Herbicides used in cotton production in Texas - Grichar, James; Dotray, Peter A.; McGinty, Joshua (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Studies were conducted during 2015 through 2018 in south-central, Coastal Bend, and Southern High Plains areas of Texas to evaluate fluridone herbicide systems for weed control and cotton response. Fluridone alone at 0.17 to 0.23 kg ai ha-1 followed by postemergence (POST) herbicides controlled Amaranthus Palmeri 82 to 100% season-long while Cucumis melo control ranged from 92 to 100%. Control of Urochloa Texana with fluridone alone ranged from 40 to 96% early-season while late-season control ranged from 37 to 96%. Fluridone plus fomesafen systems controlled A. Palmeri, C. Melo, and U. Texana at least 98% early season; however, late-season control of A. Palmeri was less than 70% while C. Melo control was 91% and U. Texana control was 80%. Adding a POST application of glyphosate to fluridone plus fomesafen improved control to at least 98% for all three weed species. Fluridone plus fluometuron combinations provided similar control to fluridone plus fomesafen. Adding glyphosate (POST) improved A. Palmeri control to at least 82% season-long. Cotton yields reflect the level of weed control with significantly better yields from fluridone systems compared with the weedy check. However, in the one year when the untreated was maintained weed-free, no differences in cotton yield were noted between the weed-free and any herbicide treatment.